2013
DOI: 10.1152/jn.01101.2012
|View full text |Cite
|
Sign up to set email alerts
|

Movement paths in operating hand-held tools: tests of distal-shift hypotheses

Abstract: Sülzenbrück S, Heuer H. Movement paths in operating hand-held tools: tests of distal-shift hypotheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…In line with this proposal, studies on tool use have suggested a shift from body-or motor-related representations to more remote, tool-based representations given that certain constraints are met (Maravita & Iriki, 2004;Sülzenbrück & Heuer, 2013). Accordingly, visual attention is readily deployed to the end point of a tool in addition to, or even instead of, the location of the operating hand (Collins, Schicke, & Röder, 2008;Reed, Betz, Garza, & Roberts, 2010;Sülzenbrück, 2012;Sülzenbrück & Heuer, 2013).…”
Section: -519)mentioning
confidence: 95%
“…In line with this proposal, studies on tool use have suggested a shift from body-or motor-related representations to more remote, tool-based representations given that certain constraints are met (Maravita & Iriki, 2004;Sülzenbrück & Heuer, 2013). Accordingly, visual attention is readily deployed to the end point of a tool in addition to, or even instead of, the location of the operating hand (Collins, Schicke, & Röder, 2008;Reed, Betz, Garza, & Roberts, 2010;Sülzenbrück, 2012;Sülzenbrück & Heuer, 2013).…”
Section: -519)mentioning
confidence: 95%